A novel property graph model for knowledge representation on the Web - Moon, Heekyung; Zhao, Zhanfang; Choi, Jintak; Han, Sungkook (International Journal of Engineering and Technology, 2018)
Graphs provide an effective way to represent information and knowledge of real world domains. Resource Description Framework (RDF) model and Labeled Property Graphs (LPG) model are dominant graph data models widely used in Linked Open Data (LOD) and NoSQL databases. Although these graph models have plentiful data modeling capabilities, they reveal some drawbacks to model the complicated structures. This paper proposes a new property graph model called a universal property graph (UPG) that can embrace the capability of both RDF and LPG. This paper explores the core features of UPG and their functions.Â